Influence of Recycled Concrete and Ground Glass on the Compressive Strength of Concrete at 7 and 28 days - Cordova, Jaime (2025)
The main objective of the article is to assess the influence of using recycled aggregates on the compressive strength of concrete (f'c = 175 kg/cm2) at the age of 7 and 28 days. Specifically, the study focuses on the partial replacement of natural coarse and fine aggregates with recycled counterparts. To achieve this, recycled concrete from the demolition of columns in Villa el Salvador, Lima—Peru, was utilized as a substitute for the natural coarse aggregate. Additionally, ground glass sourced from glass shops in the Center of Lima was employed as a substitute for the natural fine aggregate. Three mixtures were designed following the ACI method: CC, representing conventional concrete; D1, denoting concrete with a 30% substitution (20% recycled concrete and 10% ground glass); and D2, indicating concrete with a 50% substitution (30% recycled concrete and 20% ground glass). Subsequent to the formulation of these mixtures, quality verification tests were conducted on the fresh concrete, and cylindrical specimens measuring 10 × 20 cm were created for sampling. After 7 days of curing, the specimens underwent compression tests, revealing strengths exceeding 65% of the design strength and after 28 days, strengths greater than 100% of the design strength.